Threshold stress intensity factor for hydrogen-assisted cracking of CR-MO steel used as stationary storage buffer of a hydrogen refueling station. (16th March 2017) - Matsumoto, T.; Kubota, M.; Matsuoka, S.; Ginet, P.; Furtado, J.; Barbier, F.
Abstract: In order to determine appropriate value for threshold stress intensity factor for hydrogen-assisted cracking ( K IH ), constant-displacement and rising-load tests were conducted in high-pressure hydrogen gas for JIS-SCM435 low alloy steel (Cr-Mo steel) used as stationary storage buffer of a hydrogen refuelling station with 0.2% proof strength and ultimate tensile strength equal to 772 MPa and 948 MPa respectively. Thresholds for crack arrest under constant displacement and for crack initiation under rising load were identified. The crack arrest threshold under constant displacement was 44.3 MPa m 1/2 to 44.5 MPa m 1/2 when small-scale yielding and plane-strain criteria were satisfied and the crack initiation threshold under rising load was 33.1 MPa m 1/2 to 41.1 MPa m 1/2 in 115 MPa hydrogen gas. The crack arrest threshold was roughly equivalent to the crack initiation threshold although the crack initiation threshold showed slightly more conservative values. It was considered that both test methods could be suitable to determine appropriate value for K IH for this material.